2017
DOI: 10.2147/dddt.s127568
|View full text |Cite
|
Sign up to set email alerts
|

Profile of romosozumab and its potential in the management of osteoporosis

Abstract: Increased understanding of bone biology has led to the discovery of several unique signaling pathways that regulate bone formation and resorption. The Wnt signaling pathway plays a significant role in skeletal development, adult skeletal homeostasis, and bone remodeling. Sclerostin is an inhibitor of the Wnt signaling pathway. Romosozumab, a humanized monoclonal antibody that binds to sclerostin, prevents sclerostin from exerting this inhibitory effect. Therefore, in the presence of romosozumab, the Wnt signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 46 publications
(79 reference statements)
0
56
0
5
Order By: Relevance
“…50,51 Preclinical data corroborated the proof-of-concept that absence of sclerostin or inhibition with monoclonal antibodies enhanced bone strength and conferred resistance to bone fractures. 52 Thus, several sclerostin antibodies, including romosozumab (AMG-785) 53 and BPS804, 54 are being clinically evaluated, the evaluation of romosozumab being most advanced (table 2). In a phase 2 study of romosozumab versus placebo, alendronate, and teriparatide in 419 postmenopausal women, 55 romosozumab for 12 months increased BMD at the lumbar spine and the hip.…”
Section: New Drugs On the Horizonmentioning
confidence: 99%
“…50,51 Preclinical data corroborated the proof-of-concept that absence of sclerostin or inhibition with monoclonal antibodies enhanced bone strength and conferred resistance to bone fractures. 52 Thus, several sclerostin antibodies, including romosozumab (AMG-785) 53 and BPS804, 54 are being clinically evaluated, the evaluation of romosozumab being most advanced (table 2). In a phase 2 study of romosozumab versus placebo, alendronate, and teriparatide in 419 postmenopausal women, 55 romosozumab for 12 months increased BMD at the lumbar spine and the hip.…”
Section: New Drugs On the Horizonmentioning
confidence: 99%
“…After 1 year, the markers suggest that the drug's actions have been converted essentially to the behaviour of a pure antiresorptive. With this is mind, it was prescient to design FRAME and ARCH to be a 1‐year‐only exposure to romosozumab, which corresponds to the period when it is acting as an osteoanabolic and antiresorptive agent together (Figure ) .…”
Section: Dual Actions Drug: Romosozumabmentioning
confidence: 99%
“…Animal studies with romosozumab in ovariectomized rats and primates showed increases in bone mass and strength owing to the increased bone formation and reduced resorption [104,105]. Early human trials of romosozumab showed that the agent reaches peak serum concentration within a week, demonstrating a high binding affinity for sclerostin while displaying non-linear kinetics with biphasic elimination (t1/2=11-18 and 6-7 days) [106][107][108].…”
Section: Emerging Therapies 231 Anabolic Agents With Antiresorptivementioning
confidence: 99%